2014
DOI: 10.1111/ejn.12517
|View full text |Cite
|
Sign up to set email alerts
|

Sequential acquisition of cacophony calcium currents, sodium channels and voltage‐dependent potassium currents affects spike shape and dendrite growth during postembryonic maturation of an identified Drosophila motoneuron

Abstract: During metamorphosis the CNS undergoes profound changes to accommodate the switch from larval to adult behaviors. In Drosophila and other holometabolous insects, adult neurons differentiate either from respecified larval neurons, newly born neurons, or are born embryonically but remain developmentally arrested until differentiation during pupal life. This study addresses the latter in the identified Drosophila flight motoneuron 5. In situ patch-clamp recordings, intracellular dye fills and immunocytochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 65 publications
(115 reference statements)
1
29
0
Order By: Relevance
“…All MN5 dendrites (Ryglewski et al, 2014a) as well as cholinergic and GABAergic inputs form during pupal life (Kuehn and Duch, 2013). We employed targeted genetic manipulation to selectively alter cholinergic or GABAergic synaptic activity in different parts of the developing MN5 arbor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All MN5 dendrites (Ryglewski et al, 2014a) as well as cholinergic and GABAergic inputs form during pupal life (Kuehn and Duch, 2013). We employed targeted genetic manipulation to selectively alter cholinergic or GABAergic synaptic activity in different parts of the developing MN5 arbor.…”
Section: Resultsmentioning
confidence: 99%
“…MN5 firing causes global Ca 2+ influx into the soma and the dendrites (Figure 3A). Conversely, knockdown of the Drosophila Ca v 2 homolog cacophony reduces somatic and dendritic Ca 2+ influx upon firing and decreases dendrite arbor size (Ryglewski et al, 2014a). Therefore, overall MN5 firing activity and global Ca 2+ influx regulate total dendrite length, likely together with steroid hormones (Weeks and Levine, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…MN5 can be unambiguously identified from animal to animal and displays a stereotyped dendritic morphology comprising a total length of 6,500 μm and >4,000 branches (13). Dendritic architecture is tightly regulated during development by steroid hormones (24), calcium signaling (25), neural activity (19,20), and cell surface signals (26). We have previously shown that the Significance Approximately 100 billion neurons in our brain form 100 trillion synapses onto 100,000 miles of dendritic cable.…”
Section: Resultsmentioning
confidence: 99%
“…However, we cannot exclude the possibility that the mSOD1 alters the timing and sequencing of spinal cord maturational processes involving Ca 2+ channels. Ca 2+ channels contribute to many events during neuronal development, including cell migration (Komuro and Rakic, 1992), axonal growth (Gomez and Spitzer, 1999), and dendrite growth (Ryglewski et al, 2014). The developmental onset theory for ALS pathogenesis is refutable by the observation that G93A-SOD1 mice are born with locomotion mechanisms overtly intact and spinal cord development appears histologically normal by Nissl staining.…”
Section: Discussionmentioning
confidence: 99%